Transmission of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) from pre and asymptomatic infected individuals: a systematic review - Jefferson, T; Spencer, EA; Brassey, J; Onakpoya, IJ; Rosca, EC; Plüddemann, A; Evans, DH; Conly, JM; Heneghan, CJ (Elsevier, 2021)
Background The role of SARS-Cov-2-infected persons who develop symptoms after testing (presymptomatics) or not at all (asymptomatics) in the pandemic spread is unknown. Objectives To determine infectiousness and probable contribution of asymptomatic persons (at the time of testing) to pandemic SARS-CoV-2 spread. Data sources LitCovid, medRxiv, Google Scholar, and WHO Covid-19 databases (to 31 March 2021) and references in included studies. Study eligibility criteria Studies with a proven or hypothesized transmission chain based either on serial PCR cycle threshold readings and/or viral culture and/or gene sequencing, with adequate follow-up. Participants People exposed to SARS-CoV-2 within 2–14 days to index asymptomatic (at time of observation) infected individuals. Interventions Reliability of symptom and signs was assessed within contemporary knowledge; transmission likelihood was assessed using adapted causality criteria. Methods Systematic review. We contacted all included studies' corresponding authors requesting further details. Results We included 18 studies from a diverse setting with substantial methodological variation (this field lacks standardized methodology). At initial testing, prevalence of asymptomatic cases was 12.5–100%. Of these, 6–100% were later determined to be presymptomatic, this proportion varying according to setting, methods of case ascertainment and population. Nursing/care home facilities reported high rates of presymptomatic: 50–100% (n = 3 studies). Fourteen studies were classified as high risk of, and four studies as at moderate risk of symptom ascertainment bias. High-risk studies may be less likely to distinguish between presymptomatic and asymptomatic cases. Six asymptomatic studies and four presymptomatic studies reported culturing infectious virus; data were too sparse to determine infectiousness duration. Three studies provided evidence of possible and three of probable/likely asymptomatic transmission; five studies provided possible and two probable/likely presymptomatic SARS-CoV-2 transmission. Conclusion High-quality studies provide probable evidence of SARS-CoV-2 transmission from presymptomatic and asymptomatic individuals, with highly variable estimated transmission rates.